The effect of a morning and afternoon practice schedule on morning and afternoon swim performance - Arnett, M. G. (The Journal of Strength and Conditioning Research, 2001)
The purpose of the investigation was to examine the effect of a morning and afternoon practice schedule on morning and afternoon swim performance. Participants for this investigation included 6 men and 4 women competitive swimmers (mean age = 15.3 ± 0.95 years). Training involved 4 months of a morning and afternoon practice schedule. Volume, relative intensity, and frequency during training were the same for all swimmers. Participants swam 4 times per week in the morning and 5 times per week in the afternoon. Outcomes were measured initially and after the 4-month morning and afternoon practice schedule in both the morning and afternoon. Prior to entering the water to swim a 91.44-m freestyle stroke, each swimmer's body temperature was taken from the ear. Immediately following the swim performance, participants were asked to rate their perceived exertion (RPE) based on Borg's CR-10 rating scale. The order of the test administration for the time of day was balanced. Testing was conducted at the same time of day as the training sessions. Each wimmer completed 1 test condition per day. Diurnal variation in body temperature was not affected by a morning and afternoon practice schedule (p = 0.0001). A diurnal trend appeared for RPE following a morning and an afternoon practice schedule, but the trend was opposite that reported for body temperature (p = 0.089). However, swim time differences witnessed between the initial morning and afternoon measurement (p = 0.017) decreased for participants involved in a morning and afternoon practice schedule (p = 0.069).